1999
DOI: 10.1093/bja/83.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Rectal paracetamol has a significant morphine-sparing effect after hysterectomy

Abstract: We have evaluated the morphine-sparing effect of rectal paracetamol during the first 24 h after abdominal hysterectomy in a placebo-controlled, double-blind study. We studied 72 patients receiving patient-controlled analgesia (PCA) with i.v. morphine after a standardized anaesthetic, allocated randomly to receive rectal paracetamol 1.3 g, diclofenac 50 mg or placebo, after wound closure and at 8 and 16 h. Suppositories were blinded by the hospital pharmacy. Study violations excluded data from seven patients. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 14 publications
1
44
0
4
Order By: Relevance
“…Furthermore, the concomitant administration of morphine PCIA did not appear to have an effect on patients' level of sedation, which is in keeping with previous reports. 14 Patient satisfaction scores with postoperative analgesia were high in all study patients which suggests improved quality of postoperative analgesia in both study groups. These results are consistent with those reported by Varrassi et al 13 but are in direct contrast with those of Beaussier et al 15 who have reported decreased patient satisfaction with iv propacetamol when compared with iv parecoxib.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the concomitant administration of morphine PCIA did not appear to have an effect on patients' level of sedation, which is in keeping with previous reports. 14 Patient satisfaction scores with postoperative analgesia were high in all study patients which suggests improved quality of postoperative analgesia in both study groups. These results are consistent with those reported by Varrassi et al 13 but are in direct contrast with those of Beaussier et al 15 who have reported decreased patient satisfaction with iv propacetamol when compared with iv parecoxib.…”
Section: Discussionmentioning
confidence: 75%
“…When used as an opioid adjunct, oral or rectal acetaminophen reduces pain intensity 41 and opioid consumption by up to 30%, 42 although several systematic reviews and meta-analyses have shown no concurrent reduction in opioid-related side effects. 43 The use of oral over rectal acetaminophen is preferred, as the absorption of rectal acetaminophen is erratic and may therefore result in variable analgesic efficacy.…”
Section: Acetaminophen (Paracetamol)mentioning
confidence: 99%
“…Rectal diclofenac is widely used to treat acute postoperative pain in children [5]. Paracetamol is an analgesic recommended for routine postoperative pain management [6]. Rectal preparations of paracetamol are also available for use when oral delivery is inappropriate [6].…”
mentioning
confidence: 99%
“…Paracetamol is an analgesic recommended for routine postoperative pain management [6]. Rectal preparations of paracetamol are also available for use when oral delivery is inappropriate [6]. NSAIDs and paracetamol have different mechanisms of action and their combination could be synergistic.…”
mentioning
confidence: 99%
See 1 more Smart Citation